Situaciones de autolesión que se han presentado en una estudiante de la institución educativa Lestonnac de la ciudad de Pereira, departamento de Risaralda, Colombia. - Matta Bobadilla, Maira Alejandra (Universidad Antonio Nariño, 2021)
The objective of the study is to describe situations of self harm in students from the Lestonnac institute. This was done via means of a case study. The investigation has descriptive design with an exploratory mixed method focus which joins both quantitative and qualitative elements. Semi structured interviews and risk factor questionnaires were given to student for the purposes of data collection. Having demonstrated that the teen self-harmed for specific reasons contextualised by issues at school and at home. The self-harming behaviour began at 12 years old and lasted 3 to 5 years, the key themes that were evidenced were rejection and criticism by those closest to them within the school environment.